2019
DOI: 10.5483/bmbrep.2019.52.3.278
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-152-5p inhibits proliferation and migration and promotes apoptosis by regulating expression of Smad3 in human keloid fibroblasts

Abstract: Keloids are the most common pathological form of trauma healing, with features that seriously affect appearance and body function, are difficult to treat and have a high recurrence rate. Emerging evidence suggests that miRNAs are involved in a variety of pathological processes and play an important role in the process of fibrosis. In this study, we investigated the function and regulatory network of miR-152-5p in keloids. The miRNA miR-152-5p is frequently downregulated in keloid tissue and primary cells compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…α-SMA, Collagen I and Collagen III were overexpressed in keloid fibroblasts, and α-SMA contributed to collagen gel contraction [27,28]. Overexpression of miR-152-5p suppressed human keloid fibroblasts development by downregulating Smad3 [30]. In our study, miR-590-3p was verified as a target of LINC01615.…”
Section: Discussionsupporting
confidence: 59%
“…α-SMA, Collagen I and Collagen III were overexpressed in keloid fibroblasts, and α-SMA contributed to collagen gel contraction [27,28]. Overexpression of miR-152-5p suppressed human keloid fibroblasts development by downregulating Smad3 [30]. In our study, miR-590-3p was verified as a target of LINC01615.…”
Section: Discussionsupporting
confidence: 59%
“…The top PGE 2 -upregulated miRNA, miR–129-5p, exhibits antifibrotic actions in dermal fibroblasts by targeting COL1A1 ( 49 ). Furthermore, FGF2 upregulated the antifibrotic miR–29b-3p/5p, miR–152-5p, and let-7a-3p ( 5 , 50 , 51 ), while downregulating the profibrotic miR–145-3p ( 52 ). Other profibrotic- and antifibrotic-associated miRNAs — including miR-21 ( 53 ) and miR–27a-3p/miR–27b-3p ( 54 ) — were detected in high abundance in our analysis but were not differentially regulated by either treatment ( Supplemental Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, miR-152-5p and miR-637 had been demonstrated to be decreased in KFs. The upregulation of miR-152-5p played an irreplaceable role in putting off the progression of fibrosis in keloid by inhibiting proliferation, migration, and promoting apoptosis through the Erk1/2 and Akt pathways [ 78 ]. Interestingly, both miR-637 mimic and silencing Smad3 obtained consistent results in KFs, thereby confirmed that Smad3 was the direct target of miR-152-5p and miR-637 [ 79 ].…”
Section: Epigenetic Modification Mechanisms In Keloidmentioning
confidence: 99%